The Role of Information Technology in Improving Urban Governance - Muhammad Ade Kurnia Harahap; Kraugusteeliana Kraugusteeliana; Susatyo Adhi Pramono; Oh Zi Jian; Abu Muna Almaududi Ausat (Jurnal Minfo Polgan, 2023)
The rapid development of information technology has a significant impact on various fields of human life, including urban governance. In the context of urban governance, information technology can be used to improve efficiency, transparency, and community participation in the decision-making process that has an impact on the quality of life of city residents. The purpose of this research is to explain the role of information technology in improving urban governance because it is important in the context of increasingly complex urban development and requires appropriate and efficient decision-making. The focus of this research is qualitative. Methods for gathering information included paying close attention and taking detailed notes, with subsequent analysis including data reduction, visualisation, and inference. The study arrived at the conclusion that the role of information technology in improving urban governance is crucial and requires special attention from the government and relevant stakeholders. By improving access and quality of information technology services, enhancing digital literacy and information technology skills, increasing community participation in urban governance, and improving data security and privacy, the application of information technology in urban governance can become more effective and efficient in improving urban governance.